Increasing Employee Work Effectiveness Through The Implementation Of e-HRM In Companies - Subekti, Winda; Shaddiq, Syahrial (Journal of Management Branding, 2024)
Currently, the use of e-HRM in companies or organizations has become a very important need. Apart from being a necessity, it is also a requirement in winning business competition. The use of e-HRM provides convenience, accuracy and speed in completing work. Literature studies were used in this research to determine the relationship between the use of e-HRM in increasing employee work effectiveness. Previous or relevant research is used to strengthen the foundation of concepts, theories and related phenomena that have an influence on the research variables. A brief explanation of the use of e-HRM in this research is presented through different variations of e-HRM and examines its impact on the performance of private sector employees. The aim of this literature review is to determine the use of e-HRM in increasing employee work effectiveness using the Qualitative Systematic Literature Review (SLR) method by reviewing 10 journals as primary studies. The survey was carried out by following study planning including: Formulating questions, selecting data sources and search strategies, selecting papers, and then executing. In conclusion, employee work effectiveness can be realized with an individual approach to the tasks assigned and support from the company in preparing employee competencies. Training in use and thorough preparation for application implementation are two main aspects and can shape employee work effectiveness.